The Unsolved Problem of Surveillance for Colorectal Cancer in Ulcerative Colitis - Fabiola Delco; Amnon Sonnenberg (Canadian Journal of Gastroenterology)
The association between long standing extensive ulcerative colitis and the increased risk for developing colorectal cancer suggests that surveillance by frequent and regular colonoscopies may provide a means for reducing cancer-related morbidity and mortality. A crude calculation suggests that such a surveillance program would also be cost effective. None of several clinical trials, however, has been able to provide unequivocal evidence in favour of surveillance. The major reason for this failure relates to the prohibitively large number of patients with ulcerative colitis who need to be followed over a prolonged time period before statistically sound results would be obtained. Because models of decision analyses themselves have to rely on medical evidence, they cannot provide a substitute for deficient clinical data. The issue of surveillance colonoscopy cannot be resolved by the available knowledge or analytical tools. Hopefully, new techniques of surveillance or even a cure for ulcerative colitis will render the question mute of whether or not to screen patients with ulcerative colitis by frequent colonoscopy.